The Prohibition of Vessels Departure for Safety Navigation Reasons in the Hellenic Legal Order - Tryfon, Korontzis (International Journal of Asian Social Science, 2012)
In the Hellenic legal order is forecasted legally the institution of prohibition of vessels departure if do not keep concrete conditions that are forecasted by the Hellenic legislation. These conditions are related with the keeping of concrete conditions of safety navigation or with the guarantee of public state interests or private interests and are related mainly with economic demands of them. Between these two categories the most basic is the case of not keeping safety navigation conditions as this phenomenon can influence the safety of passengers, of crew, load and vessels and beyond them the prohibition of vessels departure has also economic consequences for them who are related with the activity of this. Besides consequences exist also for the State employees who impose the administrative prohibition meter of vessels departure and for that reason are controlled for penal, disciplinary and civil responsibilities.